PTU-141 A Pragmatic Randomised Controlled Trial of Healing Therapy in a Gastroenterology Outpatient Setting. (17th August 2016) - lee, R; Kingstone, T; Roberts, L; Edwards, S; Soundy, A; Shah, P; Haque, MS; Singh, S
Abstract : Introduction: To determine benefits of healing therapy as an adjunct to conventional management in irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD). Methods: : 200 outpatients with IBS or IBD were randomised to either conventional treatment or conventional plus 5 sessions of healing therapy. After 12 weeks Controls also had healing therapy. Outcomes used were, the Measure Yourself Medical Outcomes Profile (MYMOP). IBS-QOL and IBDQ and symptom measures. Results: There was a significant improvement in the MYMOP score at week 6 (p < 0.001) which was maintained to week 12 (p < 0.001) and 24 (p < 0.001). Improvements in MYMOP were significantly greater in the intervention group at both 6 (p < 0.001) and 12 weeks (p < 0.001) with effect sizes of 0.7 (95% CI: 0.4 to 1.1) and 0.8 (95% CI: 0.4 to 1.2). Condition specific data for IBS showed that most QoL dimensions had a significant minimum 10 point score improvement at 6 and 12 weeks. The overall score improvement was 12.9 units at week 6 (p < 0.001), 12.4 units at week 12 (p < 0.001) and 13.8 units at 24 weeks (p < 0.001). In IBD there was also similar score improvement but only up to week 12 associated with improved social (p < 0.001) and bowel (p < 0.001) functions. Between group difference identified for QoL scores in IBS at both week 6 (p < 0.001) and 12 (p < 0.001) but only for week 12 (p < 0.001) in the IBD group. Conclusion: The addition of healing therapy in IBS was associated with improvements in symptoms and QoL in IBS, and to a lesser extent in IBD. Disclosure of Interest: None Declared